Multiple SP1 binding sites confer enhancer-independent, replication-activated transcription of HIV-1 and globin gene promoters. - Proudfoot, N; Lee, B; Monks, J (1992)
We demonstrate that multiple SP1 protein:DNA binding sites confer enhancer-independent activation on the HIV-1 and globin gene promoters. This activation process can be achieved either by DNA replication of the promoter-containing plasmid or by high concentrations of input plasmid DNA used in the transfections. In the case of HIV-1, the three SP1 sites adjacent to the promoters TATA box are essential for this activation process. Furthermore, the human beta globin gene, which is normally dependent on a linked enhancer for transcriptional activity, can be made enhancer independent by insertion of SP1 binding sites adjacent to its TATA box. We speculate that (SP1)n-TATA type RNA polymerase II promoters may be generally permissive when present on actively replicating DNA templates and that this property of the HIV-1 promoter may be of importance to the activation of the DNA provirus in latently infected T cells.